Evaluation of metatranscriptomic sequencing protocols to obtain full-length RNA virus genomes from mammalian tissues - Yiqiao Li; Mariana Polychronopoulou; Ine Boonen; Antonios Fikatas; Sophie Gryseels; Anne Laudisoit; Joelle Gouy de Bellocq; Bram Vrancken; Gkikas Magiorkinis; Philippe Lemey; Magda Bletsa (PLoS ONE, 2025)
High-throughput sequencing technologies have advanced RNA virus genomics, but recovering viral genomes from mammalian tissues remains challenging due to the predominance of host RNA. We evaluated two metatranscriptomic workflows to address these challenges. Our results demonstrate that the methods differed significantly in performance, with Method B achieving a 5-fold increase in RNA yield and improved RNA integrity over Method A. These differences resulted in the recovery of 4 complete hepacivirus genomes with Method B compared to fragmented or incomplete genomes with Method A. Additionally, Method B’s library preparation workflow, incorporating rRNA depletion, enhanced viral genome recovery by reducing host RNA background. Our novel approach integrates an optimized RNA purification protocol with a customized bioinformatics strategy for improved viral genome recovery. Overall, our findings highlight the critical role of optimized homogenization, RNA purification, and library preparation in metatranscriptomic workflows, facilitating the more effective RNA virus genome recovery from complex mammalian tissues.